Mechanistic and physiological consequences of HPr(ser) phosphorylation on the activities of the phosphoenolpyruvate:sugar phosphotransferase system in gram-positive bacteria: studies with site-specific mutants of HPr. - Reizer, J (1989)
The bacterial phosphotransferase system (PTS) catalyzes the transport and phosphorylation of its sugar substrates. The protein-kinase-catalyzed phosphorylation of serine 46 in the phosphocarrier protein, HPr, inhibits PTS activity, but neither the mechanism of this inhibition nor its physiological significance is known. Site-specific HPr mutants were constructed in which serine 46 was replaced by alanine (S46A), threonine (S46T), tyrosine (S46Y) or aspartate (S46D). The purified S46D protein exhibited markedly lower Vmax and higher Km values than the wild-type, S46T or S46A protein for the phosphoryl transfer reactions involving HPr(His approximately P). Interactions of HPr with the enzymes catalyzing phosphoryl transfer to and from HPr regulated the kinase-catalyzed reaction. These results establish the inhibitory effect of a negative charge at position 46 on PTS-mediated phosphoryl transfer and suggest that HPr is phosphorylated on both histidyl and seryl residues by enzymes that recognize its tertiary rather than its primary structure. In vivo studies showed that a negative charge on residue 46 of HPr strongly inhibits PTS-mediated sugar uptake, but that competition of two PTS permeases for HPr(His approximately P) is quantitatively more important to the regulation of PTS function than serine 46 phosphorylation.